The Basis of Education and Training in the History of Ancient Turkestan Women: Dasar Pendidikan dan Pelatihan dalam Sejarah Perempuan Turkistan Kuno - Mokhidil , Davlatjonova (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the historical influence of women in ancient Turkestan, emphasizing their contributions to the development of science and education during the Timurid dynasty. Historically, intellectual women like Uvaisi Nodirabegim facilitated knowledge exchange and education among women, setting a foundation for future societal advancements. Despite societal constraints, these women produced significant works that have left a lasting impact on cultural and educational development. The research aims to bridge the knowledge gap concerning the role of women in early scientific development in Turkestan, specifically during a period when female educational involvement was typically undocumented and undervalued. Utilizing historical analysis and literature review methods, the study investigates various accounts of women scholars and educators from Islamic history, highlighting their contributions and the societal recognition of their efforts. Findings reveal that women like Jahan-otin Uvaisiy not only engaged in educational activities but also contributed to literature and cultural enrichment, challenging the traditional roles assigned to them. This study underscores the critical role of women in fostering educational and cultural growth in ancient Turkestan, suggesting that their contributions have been pivotal yet underrecognized in historical narratives. The implications of this research highlight the necessity of acknowledging and integrating the historical contributions of women into the broader scope of educational and cultural history, advocating for a reevaluation of historical narratives to include these influential figures. Keywords: Women, Society, Education, Science, Intellect.